Sustainability and environmental impact of renewable energy sources - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 2003)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. The world's dependence on fossil fuels is widely acknowledged to be a major cause of rising levels of carbon dioxide in the atmosphere. Thus there is an urgent need to develop energy sources with lower environmental impact, with attention focusing on renewable energy sources. Concise, authoritative, up-to-date and readable, this book reviews various energy technologies, as well as taking a critical look at the political, social and economic aspects. Throughout, the emphasis is on renewable energy sources (wind, wave, solar, biomass, etc), but a discussion of fossil fuels and nuclear power is also presented. This timely book, written by recognised experts, will be welcomed by those in the energy industries as well as by policy-makers, consultants and engineers. Students and lecturers will also find the material invaluable.
Keywords: Renewable energy sources -- Environmental aspects.; elektronické knihy; electronic books